The effectiveness of mediation and sulh in resolving family disputes : a study of parties' satisfaction with sulh in the state of Selangor - Sa'odah Binti Ahmad (Ahmad Ibrahim, Kulliyyah of Laws, International Islamic University Malaysia, 2010)
Family dispute, in particular divorce, has a traumatic effect and the legal system does not openly respond to the emotions and trauma experienced by parties in dispute. In order to preserve productive relationships for the future, Islam encourages negotiated settlements or settlements out of court in the form of sulh or mediation, conciliation and arbitration. The law and regulations pertaining to sulh have been enforced in Selangor since 2002. The present study examined the effectiveness of sulh in resolving family disputes in Selangor from the stakeholders' (parties of sulh) perspective. Effectiveness was measured by evaluating their satisfaction with sulh. Respondents of this study comprised of one hundred parties of sulh, selected through purposive sampling technique. The findings revealed that a large percentage of the respondents reported that they were highly satisfied and benefited from sulh; felt that sulh officers were impartial, knowledgeable and courteous; understood the issues involved; empathetic and were able to respect the right of the respondents to make decisions themselves on issues of dispute; and that they would recommend sulh to others. In addition, univariate analysis showed that male respondents were found to exhibit higher level of satisfaction compared to female respondents. Pertaining to the law on sulh, this study showed that there are loopholes that should be addressed in order to enhance the effective application of sulh. It can be concluded that sulh is a very viable alternative dispute resolution mechanism. Disputants were able to resolve their disputes amicably and the court also managed to decrease backlog cases. It is timely for other states in Malaysia to follow the example of Selangor in actively implementing sulh as the first step towards resolving dispute amicably